Intestinal blood flow evaluation using the indocyanine green fluorescence imaging method in a case of incarcerated obturator hernia: A case report. Issue 3 (7th October 2020) - Nakashima, Keigo; Ryu, Shunjin; Okamoto, Atsuko; Hara, Keigo; Ishida, Kota; Ito, Ryusuke; Nakabayashi, Yukio
Abstract: In surgery for incarcerated hernia, intestinal blood flow is an important factor in intraoperative decision‐making given that irreversible ischemia can result in intestinal necrosis. Here, we report a case of incarcerated obturator hernia in which the bowel was successfully preserved by evaluating intestinal blood flow with the indocyanine green fluorescence imaging method. A woman in her 80s was diagnosed with incarcerated right obturator hernia, and a laparoscopic operation was performed. The small bowel tissue that had been incarcerated exhibited dark red discoloration. Fluorescence examination of the bowel wall indicated that the ischemic changes were reversible, and accordingly, the bowel was not resected. The postoperative course was uneventful. The indocyanine green fluorescence imaging method is a useful new source of evidence that will improve intraoperative decision‐making regarding bowel ischemia.